PERFORMANSI KELOMPOK TANI HUTAN (KTH) DALAM PENGELOLAAN HUTAN KEMASYARAKATAN: DIMENSI KELOLA KELEMBAGAAN, KAWASAN, DAN USAHA - Hefri Oktoyoki; Benny Pratama; Safnizar Safnizar; Rika Himawan (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
This research examines the essence of Social Forestry, including community forestry, which consists of three aspects: institutional, area, and business management. The method is an exploratory approach with data taken using survey methods and field observations. The dimensions of institutional arrangements, forest area management, and enterprises are measured using indicators from the Head of Extension and Human Resources Development Agency Regulation No. P.5/P2SDM/Set/Kum.1/7/2020. The assessment results for KTH Tunas Maju's institutional performance in the area management dimension showed a score of 205 or 56.94% of the maximum indicator value of 360. The assessment for area management performance reached a score of 120, equivalent to 60% of the maximum indicator value of 200. The business management performance score was 215, or 48.86% of the maximum indicator value 440. Consequently, KTH Tunas Maju's overall score is 540, placing it in the